Nurraysa Global Sdn. Bhd. / Norsyasya Syazwina Mohamed - Mohamed, Norsyasya Syazwina (Faculty of Business and Management, 2023)
My memorable and enlightening 6 months industrial training began here at Nurraysa Global Sdn. Bhd. I chose this company as my internship placement because the company produces cosmetics products and I am really interested to learn more deeply about beauty products. Nurraysa is a company that produces local cosmetic products that provide the best quality with affordable price for the customers. This company is the only company that 1 applied for my industrial training for this last semester and 1 am hoping that 1will finish my industrial training in a positive environment with helpful colleagues and good relationships with them. My expectations have been proven since the first day I have been here as an internship trainee. In addition, I gained a lot of new and good knowledge about the marketing field in the beauty products business throughout the industrial training at this company. In this report, I would include my latest updated resume and other important information about my industrial training. For example, the company’s profile includes the company’s background, mission, vision and objectives of Nurraysa Global, and the products or services they are provided. Other than that, I also compile all the tasks that I had to finish during my internship period for 24 weeks. The most important thing, SWOT analysis of the company is also included in this report and I also have given a few recommendations for the company to improve based on the SWOT analysis. The industrial training that I attend in last semester for 24 weeks really helps me a lot for my future career and it is a wonderful ending for my degree study.